One mind: Enacting the Christian congregation among the Auhelawa, Papua New Guinea - Schram, Ryan (The Australian journal of anthropology, 2013)
This article examines the relationship between Christian worship and the production of religious identity among Auhelawa speakers of Normanby Island, Papua New Guinea. Auhelawa people live in a society in which a locally developed form of Christianity has emerged from a long engagement with missionaries. In the colonial era, missionaries spoke in terms of light and darkness to mediate their contradictory aims of both authentic personal conversion and total social change. Today Auhelawa believe that their society has been changed, and that this change entails a new way of thinking as well as acting, though like the missionaries they also struggle to express the relationship between the two. Viewing themselves as already converted, Auhelawa today use an ideology of ‘one mind’—unity in purpose which is subjectively felt and outwardly expressed—to resolve how their collective worship relates to individual belief. This framing of ritual, embedded in church prayer and music, however, is always incomplete. I argue this not only points to an important step in the process of formation of congregations, but also suggests why Christianity globally is both unitary yet also so strikingly diverse.